The successful adoption of halal logistics among Japanese logistics companies/ Nur Izzaty Mohamad Dalian, Harlina Suzana Jaafar and S. Sarifah Radiah Shariff - Mohamad Dalian, Nur Izzaty; Jaafar, Harlina Suzana; Radiah, S. Sarifah (Universiti Teknologi Mara Selangor, 2022)
The increasing number of Muslim populations around the world has influenced the growth of the halal business market. This triggers the Japanese halal logistics companies to take this opportunity to be certified as halal logistics service providers. It is interesting to explore the successful adoption of halal logistics among Japanese logistics companies as there are few studies and research on their success stories. This study analyses the scale of involvement of Japanese logistics companies in halal business services as well as the justification of their interest in adopting halal logistics. Based on a qualitative research approach, three in-depth interviews were conducted with the representatives of three Japanese halal-certified logistics providers in Malaysia. Four themes were identified as the elements that create the interest: culture, internationalisation, management support and government support. The findings also highlight that culture, seeking support, and integrity was significant to the sustainability of Japanese logistics companies after getting the halal certification.